2002
DOI: 10.1093/carcin/23.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mutant thyroid hormone nuclear receptors is associated with human renal clear cell carcinoma

Abstract: Thyroid hormone (T(3)) regulates proliferation and differentiation of cells, via its nuclear receptors (TRs). These processes have been shown to be abnormally regulated during carcinogenesis. We have previously found aberrant expression of TRalpha and TRbeta mRNAs in renal clear cell carcinoma (RCCC), suggesting possible involvement of TRs in the carcinogenesis of RCCC. To understand the molecular actions of TRs in RCCC, cDNAs for TRbeta1 and TRalpha1 were cloned from 22 RCCC tissues and 20 surrounding normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 49 publications
3
67
1
2
Order By: Relevance
“…Deleted areas are in large brackets. Dotted lines represent the non-in frame new sequences with numbers of aminoacids in small brackets, and STOP indicates the appearance of abnormal termination codons work, these authors have reported mutations in seven TRb and three TRa RNAs in a series of 22 renal carcinomas (Kamiya et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Deleted areas are in large brackets. Dotted lines represent the non-in frame new sequences with numbers of aminoacids in small brackets, and STOP indicates the appearance of abnormal termination codons work, these authors have reported mutations in seven TRb and three TRa RNAs in a series of 22 renal carcinomas (Kamiya et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In renal and hepatocellular carcinoma, 41,42 mutations have been found to affect either hormonebinding 43 or DNA-binding domains. 44 Chromosome 3p LOH in the vicinity of the TRb1 gene and TRb1 gene promoter hypermethylation are common in breast cancer, and are associated with decreased or absent nuclear expression of TRb1.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting defects in T3 sensing produce a variety of endocrine defects and, rarely, pituitary neoplasias, but do not typically manifest as overt peripheral neoplasia (Ando et al, 2001;Kamiya et al, 2003). Conversely, somatic mutations in human TRs are found at high frequency in human hepatocellular carcinoma (HCC), renal clear cell cancer (RCCC), and certain thyroid and gastric neoplasia (Lin et al, 1997b(Lin et al, , 1999(Lin et al, , 2001Kamiya et al, 2002;Wang et al, 2002). Whereas RTH-Syndrome mutations map almost exclusively to the TRb locus, mutations in both TRa and TRb are detected in human HCC and RCCC (Lin et al, 1997b(Lin et al, , 1999(Lin et al, , 2001Kamiya et al, 2002).…”
Section: Introductionmentioning
confidence: 99%